2015
DOI: 10.5194/isprsannals-ii-3-w4-135-2015
|View full text |Cite
|
Sign up to set email alerts
|

Isprs Benchmark for Multi-Platform Photogrammetry

Abstract: Airborne high resolution oblique imagery systems and RPAS/UAVs are very promising technologies that will keep on influencing the development of geomatics in the future years closing the gap between terrestrial and classical aerial acquisitions. These two platforms are also a promising solution for National Mapping and Cartographic Agencies (NMCA) as they allow deriving complementary mapping information. Although the interest for the registration and integration of aerial and terrestrial data is constantly incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
111
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 143 publications
(112 citation statements)
references
References 12 publications
1
111
0
Order By: Relevance
“…Although recent benchmarks and software evaluations exist (Nex et al, 2015;Aanaes et al, 2016;Knapitsch et al, 2017;Schoeps et al, 2017), the paper focuses on more complex environments, surveyed with different platforms / cameras and comparison metrics are given following a standard terminology (Luhmann et al, 2014;Granshaw, 2016). …”
Section: Paper Objectivesmentioning
confidence: 99%
“…Although recent benchmarks and software evaluations exist (Nex et al, 2015;Aanaes et al, 2016;Knapitsch et al, 2017;Schoeps et al, 2017), the paper focuses on more complex environments, surveyed with different platforms / cameras and comparison metrics are given following a standard terminology (Luhmann et al, 2014;Granshaw, 2016). …”
Section: Paper Objectivesmentioning
confidence: 99%
“…When imaged from more oblique viewpoints, either from space or more commonly from airborne sensors, building facades can also be observed sufficiently for 3D reconstruction. We plan to refine our pipeline to include true 3D volumetric assessment compared to high-resolution multilook airborne lidar (e.g., Roth et al 2007) and terrestrial lidar (e.g., Nex et al 2015 andWang et al 2016) for assessment of dense 3D reconstruction for complex building facades.…”
Section: Future Workmentioning
confidence: 99%
“…The ISPRS scientific research agenda reported in Chen et al (2015) identified an ongoing need for benchmarking in photogrammetry (Commission II) and open geospatial science in spatial information science (Commission IV). Recent efforts toward this goal include work by Rottensteiner et al (2014), Nex et al (2015), Campos-Taberner et al (2016), Koch et al (2016), and Wang et al (2016). Most publicly available benchmark datasets for 3D urban scene modeling have consisted of high resolution airborne imagery and lidar suitable for 3D modeling on a relatively modest scale.…”
Section: Introductionmentioning
confidence: 99%
“…The data set used in this paper is a sample of images availed to researchers in the framework of the multi-platform photogrammetry benchmark (Nex et al 2015) undertaken by a scientific initiative of ISPRS and EuroSDR. Figure 1 shows a sample pair used in our experiments.…”
Section: * Corresponding Authormentioning
confidence: 99%